AI-BASED DETECTION OF CULTURAL MISUNDERSTANDINGS IN ENGLISH–UZBEK FOREIGN LANGUAGE LEARNING (International journal of artificial intelligence, 2026)
This study explores the application of artificial intelligence (AI) in detecting cultural misunderstandings in English–Uzbek foreign language learning. Cultural misunderstandings often stem from differences in pragmatic norms, politeness strategies, and sociocultural expectations. Drawing on intercultural pragmatics, second language acquisition theory, and educational technology, the article examines how AI-based tools using natural language processing and machine learning can identify pragmatic mismatches in learner discourse. The study argues that AI-assisted detection enhances learners’ pragmatic competence and intercultural awareness. Pedagogical implications for English language teaching in Uzbekistan are discussed.